Grief Counselling and Grief Therapy / A Handbook for the Mental Health Practitioner - Worden William J (Rouledge, 1983)
This book provides counselling techniques to help identify and treat the grief of the bereaved. Preface, Introduction, Attachment and Loss and the Experience of Grief, Attachment Theory, Understanding the Mourning Process, Tasks of Mourning, Grief of Mourning: Facilitating Uncomplicated Grief, Goals of Grief Counselling, Abnormal Grief Reactions: Complicated Mourning, Why People Fail to Grieve, Grief Therapy: Resolving Complicated Mourning, Goals and Setting for Grief Therapy, Grieving Special Types of Losses, Suicide, Sudden Death, Grief and Family Systems, Death of a Child, The Counselor's Own Grief, Stress and Burnout, Training for Grief Counselling, Bibliography, Index.